FAO priniciples of surplus and consultative obligations of Member Nations (FAO RomeIT, 1992)
Provides a guide to the consultation and reporting obligations of Member Nations with respect to food aid and other concessional transactions, and the mechanisms and procedures for carrying out these obligations. Presents and explains the most important source material relating to the FAO Principles and to the Consultative Subcommittee on Surplus Disposal.
DC